“Good governance”, democracy and development paradigms - Hans Peter Repnik; Ralf-Matthias Mohs (Intereconomics, 1992)
“Good governance” has become a central term in the international discussion on development co-operation. What is actually meant by “good governance”? By which yardstick can it be measured? How is governance related to development, political participation and democracy? What implications does this have for bilateral and multilateral donors?
Keywords: 330; North-South Relations